Excluzul Enterprise / Zulqarnain Wahid ... [et al.] - Wahid, Zulqarnain; Mohd Farid, Muhammad Fadhlan Iqmal; Mohamad Suhaimi, Nursyakirah Husna; Mohd Faisal, Nur Adrieana; Wan Rosdi, Wan Nurina Sulwani (2025)
The name of “Excluzul” is inspired by the word of “exclusive”, from the word itself it showed that our brand is focusing on the producing an exclusive product. Thus, Excluzul aims to be one of luxury watch brand that offers high quality, elegance design and precision products. The Speciality of Excluzul brand is that we are offering a new technology in our product which are a hologram watch that allows users to see the screen light in 3D form. Furthermore, this business also offering an ai technology and health sensor to track any fitness activity such as walking step and hear rate count. The Excluzul also will be offering a customize watch design to fit with customer’s preferences. The market target of Exluzul brand is including watch enthusiasts and collectors because the products we are offering is unique and quite limited production which is called by “limited edition”. Exluzul also aiming an affluent consumer that has always seeking for exclusive and elegance items that values quality, heritage and exclusivity. Excluzul is aiming for a long-term success in competitive watch industry by having a strong business plan that offers online and retail channels. Excluzul is expecting a strong growth in the next 3 years of the business which is aiming around RM RM 369,567,360sales forecast.